Online Identity Analysis of Public Figure Rachel Vennya: Analisis Identitas Daring Tokoh Publik Rachel Vennya - Dewi, Liza Amalia (Procedia of Social Sciences and Humanities, 2025)
One of the famous people in Indonesia who has a big influence on social media is Rachel Vennya. This analysis will look at how Rachel Vennya creates her online persona, handles interactions with various audiences, and negotiates the benefits and concerns of participatory surveillance and privacy. The results of the analysis are that Rachel Vennya has been financially successful and has a solid web presence. In the face of extensive participatory surveillance, however, they have difficulty managing their content, maintaining relative authenticity, and maintaining their privacy. Highlights: Strategic Online Persona – Rachel Vennya carefully curates her content to maintain an engaging and influential online presence while balancing personal branding and relatability. Audience Engagement & Surveillance – She actively interacts with diverse audiences, leveraging participatory surveillance for visibility but facing challenges in content control and authenticity. Privacy vs. Public Exposure – Despite financial success, she struggles with maintaining privacy as constant public scrutiny complicates personal boundaries and online image management. Keywords: Rachel Venya, Online Identity, Characters